Financial Factors Affecting Fixed Asset Revaluation with Liquidity as a Moderating Variable - Kurnia Saputri, Aprilia; Kholilah, Kholilah (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to examine financial factors on fixed asset revaluation decisions, with liquidity as a moderating variable. Implementing secondary data from 122 BEI studies from 2020–2023, 488 observations were analyzed using logistic regression. The results indicate both positive and negative impacts. Leverage does not show a significant effect. Furthermore, liquidity strengthens the influence of fixed asset intensity and the market-to-book ratio, but does not moderate firm size or leverage. These findings demonstrate two theories: signaling and positive accounting, and confirm that financial characteristics and liquidity play a significant role in revaluation decisions.